2004
DOI: 10.1111/j.0022-202x.2004.23492.x
|View full text |Cite
|
Sign up to set email alerts
|

Yin-Yang 1 Negatively Regulates the Differentiation-Specific Transcription of Mouse Loricrin Gene in Undifferentiated Keratinocytes

Abstract: Loricrin is a major component of the epidermal cornified cell envelope, and is expressed only in terminally differentiated keratinocytes. This cell differentiation-specific expression pattern suggests specific suppression of loricrin gene expression in undifferentiated keratinocytes as well as its activation in differentiated keratinocytes. We identified a negative regulatory sequence element in the first intron of the mouse loricrin gene involved in suppression of loricrin gene expression in undifferentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
(28 reference statements)
2
15
0
Order By: Relevance
“…Importantly, an antibody directed against YY1, but not SP1, disrupted the putative YY1-DNA binding complex, suggesting that the complex contained the YY1 transcription factor. Disruption of the binding complex by the YY1 antibody has been reported previously 2123and similar findings were obtained using 35S labeled recombinant YY1 (Supplemental Fig. S1, please see http://hyper.ahajournals.org.…”
Section: Resultssupporting
confidence: 86%
“…Importantly, an antibody directed against YY1, but not SP1, disrupted the putative YY1-DNA binding complex, suggesting that the complex contained the YY1 transcription factor. Disruption of the binding complex by the YY1 antibody has been reported previously 2123and similar findings were obtained using 35S labeled recombinant YY1 (Supplemental Fig. S1, please see http://hyper.ahajournals.org.…”
Section: Resultssupporting
confidence: 86%
“…It is also consistent with the downregulation of LOR described by Hohl [26], who also noticed the similarity between FLG and LOR expression changes. This change may be important in light of the well-known strict regulation of the LOR gene at the transcriptional level [15, 27]. In situ hybridization analyses have shown that LOR transcripts are localized only in the upper spinous and granular layers of the normal epidermis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a potential binding site for YY1 was found. YY1 is a prominent repressor of transcription, also in epidermal cells (69,70). Neither repressor has yet been connected to HH/GLI signaling, and additional studies are necessary to address their potential involvement in the repression of FST expression.…”
Section: Discussionmentioning
confidence: 99%